2010
DOI: 10.1080/1034912x.2010.524407
|View full text |Cite
|
Sign up to set email alerts
|

Why are Older Faculty Members More Accepting of Students with Attention‐deficit Hyperactivity Disorder? A Life‐course Interpretation

Abstract: The presence of university students in the United States with disabilities is not a new phenomenon. However, little is known about the attitudes of university faculty concerning less visible disabilities such as attention-deficit hyperactivity disorder (ADHD). Using a sample of faculty at a university in the United States (n = 136), the impact of age on faculty's acceptance of ADHD was examined. Results indicated a higher percentage of older faculty members, compared with middle-aged and younger faculty, selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 28 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…12%) did not believe that ADHD students should be afforded classroom accommodations (Vance & Weyandt, 2008). Other studies have also found that professors were less likely to believe that ADHD students should receive accommodations in comparison to other learning disabilities (Buchanan, Charles, Rigler, & Hart, 2010).…”
Section: Framing the Conversation About Neurodiversity In Academic Se...mentioning
confidence: 92%
See 1 more Smart Citation
“…12%) did not believe that ADHD students should be afforded classroom accommodations (Vance & Weyandt, 2008). Other studies have also found that professors were less likely to believe that ADHD students should receive accommodations in comparison to other learning disabilities (Buchanan, Charles, Rigler, & Hart, 2010).…”
Section: Framing the Conversation About Neurodiversity In Academic Se...mentioning
confidence: 92%
“…A smaller body of literature has examined the perceptions of faculty towards university students with ADHD and the self–perceptions of students with learning disabilities (Vance & Weyandt, 2008; Buchanan et al, 2010). Studies indicate that ADHD, especially among adults, is highly variable in terms of symptomology, and furthermore, is highly context specific (Lasky et al, 2016).…”
Section: Framing the Conversation About Neurodiversity In Academic Se...mentioning
confidence: 99%
“…Buchanan and colleagues (2010) examined age as a determinant of faculty's attitudes toward disability. They found that older faculty had more positive attitudes toward students with disabilities compared to middle-aged and younger faculty members (Buchanan et al, 2010). However, others who have looked at age/ years of service have not replicated the same findings.…”
Section: Literature Reviewmentioning
confidence: 93%
“…Researchers have also investigated attitudes toward different disabilities. For example, researchers have examined professors' attitudes toward dyslexia (Stampoltzis et al, 2015), attention-deficit hyperactivity disorder (Buchanan et al, 2010), and learning disabilities (Hansen et al, 2017). Some have also examined post-secondary teachers' attitudes toward disability categories.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In an in-depth interview study with 14 faculty members at a large research university, instructors viewed learning disabilities more negatively than other types of disabilities and questioned accommodations for them, expressing concerns about accommodations infringing on their academic freedom and questioning whether learning disabilities are even legitimate (Jensen, McCrary, Krampe, & Cooper, 2004). Likewise, with accommodations for students with attention-deficit hyperactivity disorder (ADHD), which is not physically apparent, faculty responses to providing accommodations varied widely; and some faculty members attributed ADHD to poor character, discipline, or motivation (Buchanan, Charles, Rigler, & Hart, 2010). Even with supportive faculty, it is not surprising that many students do not want to risk disclosing their disabilities to negotiate accommodations.…”
Section: Graduate Students With Disabilitiesmentioning
confidence: 95%